The investigation of sodium thiosulfate effects on the toxicokinetics of cyanide and thiocyanate - İbrahim Pirinçci; Sadettin Tanyıldızı; Sezai Kaya; Bünyamin Traş (Eurasian Journal of Veterinary Sciences)
This study was made to determine the some toxicokinetic parameters of cyanide and thiocyanate in sheep experimentally poisoned with amygdalin In this study, 24 sheep 50 - 60 kg weights were used. Amygdalin and sodium thiosulfate were given and the cyanide and thiocyanate levels in samples were determined Then some toxicokinetic parameters of the cyanide and thiocyanate in the blood samples taken at 0.5, 1,2,4, 8, 24, 48 and 72 th hours were established. The sodium thiosulfate were given intravenously in doses 50 and 600 mg!kg and then the distribution haif-lives of blood cyanide levels were respectively, 0.57±0.05 and 3.24±O.16 hours; the elimination haf-lives were respectively, 172.93±11.4 and 77.08±15.26 hours: mean residence times were respectively, 250.37±25.2 and 102.10i8.12 hours; the duration of maximal concentration were respectively, 48th hour; the maximal blood levels respectively, 0.177 and 0.186 jıg/ml were determined. Besides. area under the curve values according to doses were respectively. 26.68±2.18 and 14.20±1.94 ng.hour/ml: volume of distribution at steady state were respectively, 0.371±0.01 and 4.312±O.77 lJkg; clearance values were respectively, 1.87±1.10 and 42.23t5.64 mVhour.kg were calculated. The distribution half-lives of blood thiocyanate levels according to doses were respectively, 0.44±0.03 and 0.48.0.05 hour; the elimination half-lives were respectively, 56.17±5.34 and 128.24±8.43 hours; mean residenca times were respectively, 81.69±4.47 and 152.11±11.6 hours; the duration of maximal concentration respectively, 24 and 2th hours; the maximal blood levels were respectively, 0.03 and 0.05 ng/ml were determined. Besides, area under the curve values according to doses were respectively, 2.10±0.05 and4.31±0.04|ig.hour/ml; volume of distribution at steady state were respectively, 1.89±0.03 and 21.278±1.88 llkg: clearance values were respectively, 23.75+6.40 and 139.16±51.7 mVhour.kg were established.